Strategy aimed at reduction of sputum eosinophils decreases exacerbation rate in patients with asthma - Chlumský, J; Striz, I; Terl, M; Vondracek, J (The Journal of international medical research, 2006)
Under Global Initiative for Asthma guidelines, the clinical control of disease activity and the adjustment of treatment in patients with asthma are based on symptoms, use of rescue medication, lung function and peak expiratory flow measurement (standard strategy). We investigated whether a strategy to reduce the number of sputum eosinophils (EOS strategy) gives better clinical control and a lower exacerbation rate compared with the standard strategy. Fifty-five patients with moderate to severe asthma entered this open, randomized, parallel-group study and visited the out-patient department every 3 months for 18 months. The dose of corticosteroids was adjusted according to the standard strategy or the percentage of sputum eosinophils (EOS strategy). During the study period, the EOS strategy led to a significantly lower incidence of asthma exacerbations compared with the standard strategy group (0.22 and 0.78 exacerbations per year per patient, respectively). There were significant differences between the strategies in time to first exacerbation.
Keywords: Sputum; sputum; eozinofily; Middle Aged; mužské pohlaví; Prospective Studies; Adult; Eosinophilia; bronchiální astma; Eosinophils; ženské pohlaví; Asthma; Humans; prospektivní studie; lidé středního věku; eozinofilie; dospělí; hormony kůry nadledvin; Female; Adrenal Cortex Hormones; lidé; Male